Legal basis of sailing development within 1989-2012 - Sądecka, Dagmara; Janusz, Małgorzata (Journal of Education, Health and Sport, 2018)
Motivation: This article is dedicated for presenting legal regulations concerning sailing in Poland. In chronological attribution the period covered are years between 1989 and 2012. The start caesura is 1989, connected with system transformation, which started several changes in organizational structure of the country as well as in the structures of widely perceived physical culture. The end caesura is 2012, which was the year of the Olympic Games in London. In the article methods and research techniques used included source materials analysis, which was basic information resource under the research process. Aim: Legal acts presented within the article are only the fragment of documents of varying significance, regulating any legal ground for practicing sailing. Detailed and full analysis is not possible in the article. However, the choice of some key acts and regulations and the attempt to compare the present state with the law binding in previous years, allows forming an idea about the direction of changes in legal situation of sailing in general. It has to be stated that the trend in legislation concerning recreational sailing started to be visible at the beginning of 21st century. Within earlier periods these issues were treated as marginal in regard to economical aspects of navigation. Results: Within years 1989 to 2012 there were deep changes in the area of legal regulations, evolution of sailing and training qualifications. These changes substantially adjusted contemporary legal grounds in Poland to the demands included in rights and regulations of European Union. The enhancement was especially in the area of safety and rules of assigning various licences and registering floating objects. The changes were concerning also rising numbers of regulations and legal acts connected with sailing as well tourist or recreational as sport.